Análise quantitativa do nível de radiação ionizante natural na cidade de Botucatu - Lemes, Izabella Santos Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Radiation affecting the environment is divided into non-ionizing radiation (RNI) and ionizing radiation (RI). Natural or background radiations (BG) are derived from cosmic rays and radioisotopes present in the environment and causes biochemical changes capable of inducing carcinogenic effects which a large part of the population is unaware of. Skin cancer, for example, has as its main cause the excessive exposure to solar radiation and it is the type of tumor with the highest incidence in Brazil. The aim of this work is to analyze the levels of natural ionizing radiation in the city of Botucatu-SP. Two types of radiation detectors were used: a Geiger-Müller (GM) counter and thermoluminescent dosimeters. In addition, two weather stations were used: Instrutemp (ITWH-1170) and Oregon Scientific (AWS888N) to verify environmental variables: temperature, relative humidity (UR) and atmospheric pressure (PA). Measures with the GM were made in 27 points at different altitudes, in the city of Botucatu-SP. The readings occurred on two different days, spaced of eleven months. The mean value of the natural RI exposure obtained with GM detectors was 0.0181 mR / h (±0.006) for the first survey and 0.0175 mR / h (± 0.005) for the second. The altitudes of the analysis points ranged from 757 m to 908 m, and PA values ranged from 699.00 mmHg to 683.85 mmHg. The measured values for PA presented an uncertainty of the order of 1.2% when compared to the PA values calculated with Torricelli equation. To the Installation of TLDs, 19 of the previously determined points were chosen, where the dosimeters were positioned for 48 days. The readings obtained by the TLDs are presented in electric charge unit (nC) per hour and correspond to a mean of 0,07 nC/h (± 0,04). Although the average altitude of the city of Botucatu is higher than that of several cities in the state of São Paulo, the level of natural RI was similar to that observed in other regions

As radiações que incidem sobre o meio ambiente são divididas em radiações não-ionizantes (RNI) e radiações ionizantes (RI). As radiações naturais, ou radiações background (BG) são ionizantes e provenientes de raios cósmicos e de radioisótopos presentes no meio ambiente e geram alterações bioquímicas capazes de induzir efeitos carcinogênicos dos quais grande parte da população desconhece. O câncer de pele, por exemplo, tem como principal causa a exposição excessiva a radiações solares e é o tipo de tumor com maior incidência no Brasil. O trabalho visa analisar os níveis de radiação ionizante natural na cidade Botucatu-SP. Foram utilizados dois tipos de detectores de radiação: um contador Geiger-Müller (GM) e dosímetros termoluminescentes (TLDs). Além disso, foram utilizadas duas estações meteorológicas, Instrutemp (ITWH-1170) e Oregon Scientific (AWS888N), para verificação das variáveis ambientais: temperatura, umidade relativa (UR) do ar e pressão atmosférica (PA). As medidas com o GM foram realizadas em 27 pontos previamente determinados, posicionados em locais de variadas altitudes na cidade de Botucatu-SP. As leituras ocorreram em dois dias diferentes, espaçados de onze meses. O valor médio da taxa de exposição de RI natural obtido com os detectores GM foi de 0,0181 mR/h (± 0,006) para o primeiro levantamento e 0,0175 mR/h (± 0,005) para o segundo. As altitudes dos pontos de análise variaram de 757 m a 908 m, e os valores de PA medidos variaram de 699,00 mmHg a 683,85 mmHg. Os valores medidos para a PA apresentaram uma incerteza da ordem de 1,2% quando comparados com os valores de PA calculados com a equação de Torricelli. Para a instalação dos TLDs, foram escolhidos 19 dos pontos anteriormente determinados, onde os dosímetros ficaram posicionados por 48 dias. As leituras obtidas pelos TLDs são apresentadas em unidade de carga elétrica (nC) por hora e correspondem a uma média de 0,07 nC/h (± 0,04). Apesar da altitude média da cidade de Botucatu ser maior que a de várias cidades do estado de São Paulo, o nível de RI natural se mostrou semelhante ao verificado em outras regiões
Keywords: Atmospheric pressure; Ionizing radiation; Radiation detectors; Detectores de radiação; Pressão atmosférica; Radiação ionizante